Effect of Amphiphilic Compounds on Posthypertonic Lysis of Erythrocytes - Чабаненко, О.О.; Єршова, Н.А.; Шпакова, Н.М. (44th Annual Conference of Young Scientists â€˜Cold in Biology and Medicine. Current Issues in Cryobiology, Transplantology and Biotechnologyâ May 19, 2020, Kharkiv, Ukraine. Probl Cryobiol Cryomed 2020; 30(3): 286, 2020)
To study the damage factors, acting at the thawing stage of erythrocytes, cryopreserved under protection of penetrating cryoprotective agent, as well as transfer into recipient’s bloodstream, posthypertonic shock (PHS) is used. Recently there was demonstrated the ability of chlorpromazine to reduce posthypertonic lysis (PHL) level of human erythro-cytes [Semionova et al., ൬൪൫൱]. Research aim was to study the eff ect of anionic sodium decyl sulfate (C൫൪), cationic trifluoperazine (TFP) and non-ionic decyl-β,D-glucopyranoside (DGP) on posthypertonic lysis of human erythrocytes at ൭൱ and ൪°C.Posthypertonic shock was simulated by transferring erythro-cytes from dehydration medium (൫.൰൯ mol/L NaCl) to rehyd-ration one (൪.൫൯ mol/L NaCl) at ൭൱ and ൪°C. Amphiphilic com-pounds were added into rehydration medium prior to transfer of the cells. After the combined action of amphiphilic com-pounds and PHS, the cell suspension was kept for ൭൪ min at certain temperature range of ൪–൭൱°C. The hemolysis level of erythrocytes was measured spectrophotometrically (λ = ൯൮൭ nm). The morphological features of the cells were evaluatedby light microscopy using microscope Axio Observer Z൫ with a thermal attachment.It was established that all amphiphilic compounds, re-gardless of their physicochemical properties, reduced the PHL level of erythrocytes at ൪°C (unlike at ൭൱°C) and showed sufficiently high antihemolytic activity (൰൪–൱൪%). Thus, TFP and C൫൪ were effective within the concentration range of ൫൪൪–൬൪൪ and ൬൪൪–൰൪൪ μmol/L, respectively, while the antihemolytic activity of DGP manifested in a wider concent-ration range of ൮൪൪–൫൰൪൪ μmol/L.It was shown that when heating the cells survived after PHS eff ect at amphiphiles presence (൪°C), the development of he-molysis was observed when using TFP and DGP, but not anionic C൫൪. Comparative analysis of morphology of these cells showed that the increase temperature using TFP (൫൯൪ μmol/L) led to the transformation of erythrocytes into spherocytes witha further rise of ghosts number, while C൫൪ (൮൪൪ μmol/L) causeda slight increase in cell volume without amount changing.Thus, the high effi ciency of anionic C൫൪, cationic TFP and non-ionic DGP under PHS conditions of human erythrocytes at ൪ºC was shown, however, the cells survived after the combined action of PHS and amphiphiles (൪°C) were resis-tant to subsequent heating only when using anionic C൫൪. Apparently, this compound inhibits a reorganization of erythrocyte membrane, occurring at higher temperatures, and as a result, prevents the development of hemolytic trans-membrane pore
Вплив амфіфільних сполук на постгіпертонічний лізис еритроцитів
Chabanenko ОО, Yershova NA, Shpakova NM. Effect of Amphiphilic Compounds on Posthypertonic Lysis of Erythrocytes. In: 44th Annual Conference of Young Scientists â€˜Cold in Biology and Medicine. Current Issues in Cryobiology, Transplantology and Biotechnologyâ May 19, 2020, Kharkiv, Ukraine. Probl Cryobiol Cryomed 2020; 30(3): 286
Keywords: erythrocytes; amphiphilic compounds; cryoprotective agent; posthypertonic shock